Simulasi Pemohonan Listrik (Electrical Treeing) pada Isolasi Polimer dengan Menggunakan Metode Cellular Automata - Suwarno Suwarno; Ronald P. Hutahean (Institute for Research and Community Services (LPPM) ITB, 2005)
Recently, polymeric insulating materials are widely used for high voltage cables. During operation, a field enhancement sites such as void and protrusion may exist in the polymeric insulation. Degradation of the insulation may occur and the so-called electrical treeing will grow. The electrical treeing appears in the polymeric insulation in the form of tree-like structure with very fine cylindrical channels similar to the trunks and branches in an actual tree. The appearance of an electrical treeing is a sign that a harmful degradation is developing in the insulation. In order to avoid the electrical treeing to occur in the polymeric insulation and for diagnosing of the condition, it is important to know the behavior of the electrical treeing and the correlation with the insulation materials. This paper reports a computer simulation results of the behavior of the electrical treeing using Cellular Automata. The simulation was done in polymeric materials with various critical electric fields. The simulation results showed that selection of polymeric insulating materials with high critical field is a very important step in the design of insulation.